Tindak Tutur Ilokusi dalam Ceramah Buya Yahya di Youtube Al- Bahjah Tv - Prananda, Nur Anindita; Hermaliza (UIR Press, 2023)
The purpose of this study is to describe, analyze, interpret, and conclude the types of illocutionary speech acts in Buya Yahya's Lectures on YouTube Al-Bahjah TV. The data analysis technique used in this study is a qualitative descriptive analysis technique. In this paper, the most common illocutionary speech acts found in Buya Yahya's lectures are directive illocutionary speech acts because the speaker tries to influence or influence the speech partner to take the actions he wants in accordance with the speech delivered. The least common illocutionary act is declarative illocutionary act because declarative illocutionary aims to create new things (status or circumstances) that can be carried out by someone who has special authority in a particular institution or institution. It is hoped that the results of this study can be applied in the world of education, especially for Indonesian language educators as reference material for teaching materials on one of the studies of pragmatics, namely the types of illocutionary speech acts.